Recommendations for parents and caregivers of children at risk of gambling in light of systematic review of literature - Justyna Kusztal; Małgorzata Piasecka (Problemy Wczesnej Edukacji)
The cognitive goal of this article is to provide the knowledge needed to strengthen the educational and preventive competencies of parents and caregivers in the prevention of gambling disorders in children and adolescents. The practical goal, therefore, is to formulate recommendations for parents and caregivers in the upbringing and prevention of gambling disorders in the family and peer environment. The article is a review. This article, which is aligned with theme of the journal, refers to research on the risk factors of gambling disorders in children and adolescents and was based on an analysis of foundational data from a systematic review of English-language scholarly journals over the years 2013–2021. The results of the data analysis made possible a qualitative synthesis and formulation of recommendations for parenting and preventive practice for parents and caregivers.